2020
DOI: 10.3390/ijerph17218093
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Function Model of Attachment Security Priming: Theoretical Framework and Empirical Evidence

Abstract: According to attachment theory, security providing attachment figures fulfill two main functions: (1) safe haven—providing safety and comfort and reducing stress—helping people regain a sense of security; and (2) secure base—providing resources and a base from which people can spring into action. According to the Dual Function of Security Priming Model, security priming can result in one of two outcomes paralleling these two functions. Which outcome is likely to present itself depends on the level of stress im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Selcuk et al (2012) found that activating mental representations of attachment figures before stress-induction (recalling a negative memory) did not reduce negative affect or thinking, but activating these representations after stress-induction did. Similarly, Ai et al (2020) found that salivary cortisol concentrations increased when security priming was administered before the stressor, and decreased when administered after. This suggests that secure imagery may be more helpful in facilitating recovery from, rather than buffering, stress.…”
Section: Buffering Hypothesismentioning
confidence: 92%
“…Selcuk et al (2012) found that activating mental representations of attachment figures before stress-induction (recalling a negative memory) did not reduce negative affect or thinking, but activating these representations after stress-induction did. Similarly, Ai et al (2020) found that salivary cortisol concentrations increased when security priming was administered before the stressor, and decreased when administered after. This suggests that secure imagery may be more helpful in facilitating recovery from, rather than buffering, stress.…”
Section: Buffering Hypothesismentioning
confidence: 92%
“…Future research might examine whether the goal to feel included in safe social connections can co-opt other self-regulatory systems as means for its pursuit, such as ones that serve the needs for self-esteem, system justification, or group status. Consistent with this logic, priming the thought of a secure attachment—one where the need to feel safe in social connection is presumably fulfilled—can increase empathy for others, reduce prejudice, and increase prosocial behavior (Ai et al, 2020; Mikulincer & Shaver, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…Theoretically, attachment security serves two key functions: promoting a “safe haven” (i.e., relaxation) as well as a “secure base” (i.e., mobilization of energy to effectively cope with stressors). If so, then the positive effects of priming attachment security on performance should be particularly pronounced when there is “a threat in the air” ( Ai et al, 2020 ), as is the case when African Americans take a test said to be diagnostic of intelligence ( Steele, 1997 ).…”
Section: Discussionmentioning
confidence: 99%